2020
DOI: 10.1016/j.ssaho.2020.100074
|View full text |Cite
|
Sign up to set email alerts
|

Double pandemic: racial discrimination amid coronavirus disease 2019

Abstract: The emergence of the COVID-19 pandemic has seen an escalation of racial discrimination against non-citizens and people of colour in many places around the world. While this COVID-19-related racial discrimination against non-citizens and people of colour has drawn much attention in the media space, the issue has been less discussed in academia. Given that racial discrimination has a significant impact on human relations, mental health, and general well-being, it is important to address the rising racial discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 14 publications
0
34
0
4
Order By: Relevance
“… 7 31 32 A previous national US survey found that minority physicians were less likely to report burnout including emotional exhaustion and depersonalisation compared with white, non-Hispanic physicians, 33 whereas others demonstrated no difference in burnout. However, with increased COVID-19 infections, incidents of racial discrimination increased dramatically and this ‘double pandemic’ 31 may place greater strain on visible minority physicians. Although our study also found no difference in emotional exhaustion and depersonalisation by ethnicity, we identified a greater likelihood of feeling low personal accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“… 7 31 32 A previous national US survey found that minority physicians were less likely to report burnout including emotional exhaustion and depersonalisation compared with white, non-Hispanic physicians, 33 whereas others demonstrated no difference in burnout. However, with increased COVID-19 infections, incidents of racial discrimination increased dramatically and this ‘double pandemic’ 31 may place greater strain on visible minority physicians. Although our study also found no difference in emotional exhaustion and depersonalisation by ethnicity, we identified a greater likelihood of feeling low personal accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with previous studies that cultural differences are a strong predictor of the characteristics and nature of cyberbullies, cyberbullying frequency, or reinforcement [ 109 , 110 ]. A recent study [ 111 ] found that the escalation of COVID-19-related racial discrimination and bullying against non-citizens and people of color in many places around the world. Covid-19-related discrimination and bullying have been triggered by anti-Asian content present in several international social media.…”
Section: Discussionmentioning
confidence: 99%
“…[ 71 ] regarding the necessity of designing prevention and intervention programs for universities, and increasing students’ awareness of both cyberbullying and coping strategies to deal with it. Advocating against racial discrimination, and promoting tolerance and acceptance of ethnic and cultural differences among university students are useful methods for eliminating racial discrimination [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, societal inequalities have been exacerbated by the COVID-19 pandemic, with marginalized communities being disproportionately affected. 1,2 While all of our lives have been impacted in some way by the global COVID-19 pandemic, communities of color are simultaneously suffering from the ongoing pandemic of systemic racism.…”
Section: Importance and Visionmentioning
confidence: 99%
“…As we embark on our physician‐scientist training in the community of St. Louis, and in the United States, where science and medicine have histories steeped in injustices towards communities of color, we sought to create a platform to educate ourselves in order to uplift these communities in our careers and personal lives. Recently, societal inequalities have been exacerbated by the COVID‐19 pandemic, with marginalized communities being disproportionately affected 1,2 . While all of our lives have been impacted in some way by the global COVID‐19 pandemic, communities of color are simultaneously suffering from the ongoing pandemic of systemic racism.…”
Section: Importance and Visionmentioning
confidence: 99%